Obtaining and characterizing silage acid flour from corvine (micropogonias furniere) residues with and without of rice bran - Schoffen Enke, Dariane Beatriz [UNESP]; Souza-Soares, Leonor Almeida de (Univ Federal Ceara, Centro Ciencias Agrarias, 2016)
The objective of this work was to obtain chemical silage for bird feeding, from residues of Corvine (Micropogonias furniere), accompanying hydrolysis degree and characterizing the different obtained fractions. For the elaboration of the silage, the residues were grinded, distributed in buckets, acidified with acetic acid P.A. (10% P/V). The silage was stored at room temperature, with periodic homogenization, pH and temperature of the process being monitoring. After 15 days of experiment it was removed the bony matter by crude filtration and pressing and the filtrate was centrifuged for separation of the different fractions: liquid, proteinic and greased. The other proteinic fraction was dried in greenhouse with and without addition of rice bran. The proximal composition of the raw material and of the obtained fractions were determined and also determined the soluble nitrogen for the hydrolysis degree verification. The obtained silage presented a proteinic value of 59,54%. Part of the proteins, present in the raw material, they were retained in the minerals flour and liquid fractions obtained in the silage process. The room temperature varied within 20 and 28 degrees C and the pH remained below 4,5 during the process. The tenor of soluble nitrogen increased during the hydrolysis period reaching 62%.
Keywords: deffated rice bran; Hydrolysis degree; Micropogonias furniere; Fish waste